Molecular phylogenetic inference of White-Spotted Guitarfish (Rhynchobatus australiae) collected from local Malaysian fish markets - BADRUL MUNIR MD-ZAIN; SHAHIDATINA AISHAH ABDUL-MUTALIB (Biodiversitas Journal of Biological Diversity, 2018)
Md-Zain BM, Abdul-Mutalib SA, Aifat NR, Masstor NH, Mohd-Yusof NS, Mohd-Hashim A, Abdul-Latiff MAB, Yaakop S, Samat A. 2018. Molecular phylogenetic inference of White-Spotted Guitarfish (Rhynchobatus australiae) collected from local Malaysian fish markets. Biodiversitas 19: 1382-1386. The white-spotted guitarfish (Rhynchobatus australiae) is in high demand at local Malaysian fish markets because its fins are a valuable food source. To date, few molecular studies have characterized their genetic identity. We have conducted a molecular study to infer the phylogenetic relationships of white-spotted guitarfish, which portray a similar morphology to sharks and rays. The main objective of this study was to determine the phylogenetic position of R. australiae using cytochrome oxidase I (COI) sequences of mitochondrial DNA based on fish samples collected from local Malaysian fish markets. This study included nine genetic samples of R. australiae and fourteen samples from other members of the shark and ray families, including Sphyrna lewini (Sphyrnidae), Rhizoprionodon oligolinx and Carcharhinus sorrah (Carcharhinidae), Dasyatis zugei, Himantura walga, Himantura gerradi, Himantura jenkinsii and Neotrygon kuhlii (Dasyatidae). Chimaera fulva, a member of the Chimaera family, was used as the outgroup. Sequences in size of ~701 base pairs were successfully obtained from all fish samples. The phylogenetic tree topology was reconstructed using distance-based (neighbor-joining) and character-based (maximum parsimony) methods using MEGA and PAUP software. Results indicated that R. australiae formed monophyletic clade and is closely related to sharks (Sphyrnidae and Carcharhinidae). This conclusion was also supported by genetic distance analysis which indicated that Rhynchobatidae and sharks (Carcharhinidae and Sphyrnidae) were closer to each other than to rays (Dasyatidae). This study has proven the efficiency of the COI mitochondrial locus in revealing the phylogenetic position of R. australiae. Research findings from this study have increased our understanding of the phylogenetic relationships among guitarfish, sharks, and rays, and their respective taxonomic positions are given their shared morphological characters. This will benefit us in identifying these fish species before consumption from local fish markets.